The Influence of Fintech Companies Cashback Methods on Student Consumption Behavior (A Study on Economics Students at Brawijaya University) - Rahmadian, Muhammad Farel; Nurul Badriyah (Journal of Development Economic and Social Studies, 2025)
Indonesia This study aims to analyze the effect of the cashback indicator on consumption behaviour of students of economics, faculty of economic and business, universitas brawijaya. The method used is quantitative with multiple linear regression analysis. Then the data used is primary data in the form of questionnaire. The results showed that the amount in cashback had a significant effect on the consumption behaviour of stundent of economics and business, Brawijaya University the compability of promises in cashback had a significant effect on the consumption behaviour of student of economics.